Artificial intelligence and natural language : 6th conference, AINL 2017, St. Petersburg, Russia, September 20-23, 2017, revised selected papers /: 6th conference, AINL 2017, St. Petersburg, Russia, September 20-23, 2017, revised selected papers. (2017) - Unknown
No abstract available